If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(y + 30) = 6y + -4 Reorder the terms: 3(30 + y) = 6y + -4 (30 * 3 + y * 3) = 6y + -4 (90 + 3y) = 6y + -4 Reorder the terms: 90 + 3y = -4 + 6y Solving 90 + 3y = -4 + 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. 90 + 3y + -6y = -4 + 6y + -6y Combine like terms: 3y + -6y = -3y 90 + -3y = -4 + 6y + -6y Combine like terms: 6y + -6y = 0 90 + -3y = -4 + 0 90 + -3y = -4 Add '-90' to each side of the equation. 90 + -90 + -3y = -4 + -90 Combine like terms: 90 + -90 = 0 0 + -3y = -4 + -90 -3y = -4 + -90 Combine like terms: -4 + -90 = -94 -3y = -94 Divide each side by '-3'. y = 31.33333333 Simplifying y = 31.33333333
| 5(v-5)+3(v+2)=-4v+7+3v-2 | | 3(x+5)=5x+2.5 | | 117=6x-12+3x+3 | | (34-2)y=8 | | 8(5x-3)+4(1-8x)=3x-8+3x-2 | | 4u^2-2u=0 | | 10x5/2 | | 2p-10)/(8p-40) | | 6(9d)=3d | | 180=x+(0.05+x) | | (9x-2y)-(6x+2y)= | | 6(x-4)-4=8 | | 4logx-3logx=12 | | 238=16t^2+32t | | Xy=5x-2 | | x=13+0.75y | | 4lgx^3-3lgx^2=12 | | (5x-3)/3=4 | | 4logx^3-3logx^2=12 | | (-7)=g+(-5) | | 5a+1=8 | | 5a+56=-56 | | U-24=(-27) | | 5x+2y+30=0 | | 28=w-(-5) | | (12.50-1.95)x=125 | | 3/2x-4 | | C=qn+r | | -33=-17-n | | 7x-78=-65 | | (-14)=t+(-25) | | 14-6v=-4(2v-1) |